Dormancy breaking, viability and conservation of Mauritia flexuosa seeds - Spera, Maria Roseli Nicoli; Cunha, Rozane da; Teixeira, João Batista (Pesquisa Agropecuaria Brasileira, 2001)
The present work was conducted to evaluate the viability of embryos of Mauritia flexuosa L. by tetrazolium test and in vitro culture, high temperature treatment on dormancy breaking, and the effect of storage at different temperatures on seed conservation. The viability of newly harvested embryos presented a high correlation with the rate of embryo germination in vitro. The rate of viability was higher than 90% either when evaluated by the tetrazolium method or by in vitro embryo culture. Dormancy breaking of seeds was tested by treating the seeds under temperatures of 30, 35 and 40ºC for 15, 30, and 45 days. Great variation was observed among treatments, but, at least on day 15 and on day 30, the germination was higher than in the control. Seeds stored in plastic bags for four and a half months and temperature of 20ºC presented a germination rate higher than 90% while in the seeds stored at 30ºC the viability was zero.